Antibodies to Loop 6 of the P2 Porin Protein of Nontypeable Haemophilus influenzae Are Bactericidal against Multiple Strains - Neary, John M. (American Society for Microbiology, 2001)
The P2 porin protein is the most abundant protein in the outer membrane of nontypeable Haemophilus influenzae (NTHI). Analysis of sequences of P2 from different strains reveals the presence of both heterogeneous and conserved surface-exposed loops of the P2 molecule among strains. The present study was undertaken to test the hypothesis that antibodies to a conserved surface-exposed loop are bactericidal for multiple strains of NTHI and could thus form the basis of vaccines to prevent infection due to NTHI. Polyclonal antiserum to a peptide corresponding to loop 6 was raised and was immunopurified over a loop 6 peptide column. Analysis of the antibodies to whole organisms and peptides corresponding to each of the eight loops of P2 by immunoassays revealed that the antibodies were highly specific for loop 6 of P2. The immunopurified antibodies bound to P2 of 14 of 15 strains in immunoblot assays. These antibodies to loop 6 demonstrated complement-mediated bactericidal killing of 8 of 15 strains. These results support the concept of using conserved regions of the P2 protein as a vaccine antigen.